2015
DOI: 10.1007/s13197-015-2002-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and pH degradation kinetics of anthocyanins in natural food colorant prepared from black rice bran

Abstract: The study of the stability of anthocyanins in food colorant powder is important to predict the quality changes occurring as the food products are processed, to prevent and control the degradation of the anthocyanins. The objectives of this study were to identify anthocyanin components in natural food colorants obtained from black rice bran, and investigate their thermal stability at 60, 80, and 100°C, pH stability from 2.0 to 5.0 and also their correlation with visual color, L * , C * , and h°. Results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
46
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 30 publications
(44 reference statements)
10
46
1
9
Order By: Relevance
“…Therefore, it is necessary to understand the effect of various processing parameters, such as temperature and pH on the degradation of C3G and P3G. Although, the degradation behavior of C3G and P3G from black rice (Hou, Qin, Zhang, Cui, & Ren, 2013;Loypimai, Moongngarm, & Chottanom, 2016); mulberry fruit (Zhou, Chen, Bi, Wang, & Wu, 2017) was investigated. However, to the best of our knowledge, the degradation of C3G and P3G from purple rice bran under different pH values and temperatures have hardly been addressed.…”
mentioning
confidence: 99%
“…Therefore, it is necessary to understand the effect of various processing parameters, such as temperature and pH on the degradation of C3G and P3G. Although, the degradation behavior of C3G and P3G from black rice (Hou, Qin, Zhang, Cui, & Ren, 2013;Loypimai, Moongngarm, & Chottanom, 2016); mulberry fruit (Zhou, Chen, Bi, Wang, & Wu, 2017) was investigated. However, to the best of our knowledge, the degradation of C3G and P3G from purple rice bran under different pH values and temperatures have hardly been addressed.…”
mentioning
confidence: 99%
“…The results obtained in this study for the dry matter and total sugar contents agree with the results reported in the literature (Altuğ & Ve Gönül, ; Gögtüş, Maskan, & Kaya, ; Uslu, Erbaş, Turhan, & Tetik, ). It was reported that the anthocyanin pigment was found in different chemical forms (Fleschhut, Kratzer, Rechkemmer, & Kulling, ; Loypimai, Moongngarm, & Chottanom, ) and its stability was affected by various factors such as pH, heat treatment, light exposure and food matrix (Torskangerpoll & Andersen, ; Özen, Akbulut, & Artık, ). It is important to note that the storage time‐dependent changes observed in the color values especially for the samples T1 and T2 (given in Section 3.1 in Table ) were not observed in the pH values.…”
Section: Resultsmentioning
confidence: 99%
“…Hal ini dikarenakan adanya perbedaan kandungan amilosa pada masing-masing bahan baku, mengakibatkan struktur granula pati lebih kokoh dan keras karena terkait dengan kemampuan amilosa membentuk kristal (Lii et al, 1996) Beberapa penelitian melaporkan bahwa beras memiliki senyawa bioaktif yang tinggi, diantaranya adalah tokoferol, tokotrienol, γ-oryzanol, dan senyawa fenolik (Chakuton et al, 2012). Senyawa fitokimia seperti kandungan antosianin yang terdapat pada beras berpigmen berada pada bagian kulit terluar dari beras tersebut yaitu lapisan aleuron (Loypimai et al, 2016). Lapisan aleuron ini berbedabeda ketebalannya berdasarkan varietas, dimana beras yang berbentuk bulat pendek cenderung merupakan lapisan aleuron yang lebih tebal dibanding beras jenis lonjong panjang.…”
Section: Teksturunclassified